Spleen Siliconoma - Elena Alexandrovna Semenova; Anastasia A. Vasilkonova; Aminat U. Magomedova; Irina Borisovna Kaplanskaya; Maria Dmitrievna Sanatko; Mikhail M. Karpukhin; Alexander V. Grzhimolovsky; Lyubov S. Al-Radi (Mediterranean Journal of Hematology and Infectious Diseases)
Along with a silicone lymphadenitis in axillary lymph nodes there are few observations of siliconomas with other localization in the literature. We observed female patient of 34 years that had tumor mass in the spleen after 12 years from augmentation mammoplasty. Diagnostic splenectomy was performed. The mass consisted of rounded cavities up to 1,5 cm in diameter, filled with colloid. Microscopically cavities with the colloidal substrate either had no lining, or were presented by a wall of sinusoid. On the periphery of the mass there were low-grade signs of the organization in the form of minor fibroblasts proliferation, minute vessels proliferations, existence of the considerable number of histiocytes and segmented granulocytes. By means of a mass-spektrometry method (7% of silicon in the bit of spleen mass) it was proved that the found substance was a silicon. There is no data on spleen located siliconomas in the scientific literature.